Schottky Uniformizations of Z22 Actions on Riemann Surfaces - A. Hidalgo, Rubén (Revista Matemática Complutense, 2005)
Given a closed Riemann surface S together a group of its conformal automor phisms H Z2 , it is known that there are Schottky uniformizations of S real =2 izing H . In this note we proceed to give an explicit Schottky uniformizations for each of all different topological actions of Z2 as group of conformal automor 2 phisms on a closed Riemann surface.